THE INTERFAITH LELAYU TRADITION: RELIGIOUS PLURALISM IN BULUNGCANGKRING VILLAGE JEKULO KUDUS - Rifqi, Rifqi Irfan; Masudi, Masudi; Mafud, Mowafg (Al-Qalam, 2025)
This study aims to provide an in-depth description of the interfaith lelayu tradition practiced by the Muslim community and members of the Evangelical Church in Tanah Jawa (GITJ) congregation in Bulungcangkring Village, Jekulo, Kudus. The analysis focuses on the humanitarian values embodied in this tradition and examines how the community preserves harmony and respects religious boundaries during the lelayu process, which serves as a tangible expression of interreligious coexistence in local culture. The acts of offering condolences and performing tahlil reflect the spirit of tolerance and harmony among different faith communities. This research employed a qualitative approach with fieldwork as the primary data source, using observation, interviews, and documentation for data collection. The findings reveal that the lelayu tradition in Bulungcangkring Village transcends religious boundaries and provides a shared space for interfaith interaction grounded in mutual cooperation, empathy, and solidarity. Despite theological differences, community members maintain respect for their respective religious doctrines. Consequently, this tradition does not generate doctrinal conflict but rather reinforces the spirit of tolerance in social life, contributing to a broader understanding of cultural practices that foster peace and harmony within a pluralistic society.